(31)P cardiac magnetic resonance spectroscopy during leg exercise at 3 Tesla. - Hudsmith, L; Tyler, D; Emmanuel, Y; Petersen, SE; Francis, J; Watkins, H; Clarke, K; Robson, M; Neubauer, S (2009)
Investigation of phosphorus ((31)P) magnetic resonance spectroscopy under stress conditions provides a non-invasive tool to examine alterations in cardiac high-energy phosphate metabolism that may not be evident at rest. Our aim was to establish cardiac (31)P MR spectroscopy during leg exercise at 3T. The increased field strength should provide a higher signal to noise ratio than at lower field strengths. Furthermore, relatively high temporal resolution at a sufficiently fine spatial resolution should be feasible. (31)P MR spectra were obtained with a 3D acquisition weighted chemical shift imaging sequence in 20 healthy volunteers at rest, during dynamic physiological leg exercise and after recovery at 3T. Haemodynamic measurements were made throughout and the rate pressure product calculated. With exercise, the mean heart rate increased by 73%, achieving a mean increase in rate pressure product of 115%. The corrected PCr/ATP ratio for subjects at rest was 2.02 +/- 0.43, exercise 2.14 +/- 0.67 (P = 0.54 vs. rest) and at recovery 2.03 +/- 0.52 (P = 0.91 vs. rest, P = 0.62 vs. exercise). A cardiac (31)P MR spectroscopy physiological exercise-recovery protocol is feasible at 3T. There was no significant change in high-energy cardiac phosphate metabolite concentrations in healthy volunteers at rest, during physiological leg exercise or during recovery. When applied to patients with heart disease, this protocol should provide insights into physiological and pathological cardiac metabolism.